THE DEVELOPMENT OF ZAKAT INSTITUTIONS IN THE VIEW OF LEGAL REGULATIONS IN INDONESIA - Sandy Rizki Febriadi; Cecep Soleh Kurniawan (Univeristas Islam Bandung, 2022)
Indonesia is a country with the largest muslim population in the world. Muslim population in Indonesia is 80% of the approximately 220 million Indonesian population. That is, about 180 million Muslims have the obligation to pay zakat, both zakat fitrah and zakat assets. This condition should be an extraordinary zakat potential related to zakat collection efforts. However, the development of zakat management institutions has not been accompanied by the growth of public interest in paying zakat to these zakat institutions. The impact is that the management of zakat in Indonesia is not optimal, while the potential for zakat in Indonesia is very large. This research purposes to find out concept of zakat, history, legal basis, types, and its wisdom. As well as, it describes legal regulations of zakat, laws and other regulations that applied in Indonesia, especially related to the institutional aspects of zakat institutions. The research method used is a normative juridical approach, which is a method of researching a thought related to the laws that apply in society. The research result implied that Zakat is the name for a certain property, obtained from a certain property, according to a certain way and given to a certain group of people as well. Legally, the development of zakat management regulations in Indonesia began with the issuance of Law Number 23 of 2011 concerning Zakat Management, until the issuance of the Decree of the Chairman of BAZNAS Number 142 of 2017 concerning the Nishab Value of Zakat for Income in 2017.